Inference on P(Y<X) Based on Record Values for Generalized Pareto Distribution. Issue 2 (November 2020) - Chacko, Manoj; Mathew, Shiny
In this article, the estimation ofR = P ( Y < X ) is considered whenX andY are two independent generalized Pareto distributions. The maximum likelihood estimators and Bayes estimators ofR are obtained based on record values. The Asymptotic distributions are also obtained together with the corresponding confidence interval ofR . AMS 2000 subject classification: 90B25